Mannose phosphate isomerase gene mutation leads to a congenital disorder of glycosylation: A rare case report and literature review - Lu, Siliang; Liang, Shuheng; Wu, Yi; Liu, Jinyi; Lin, Lin; Huang, Guosheng; Ning, Huaijun (Frontiers in Pediatrics, 2023)
We report the case of a 2-year-old girl who was diagnosed with Mannose-6-phosphate isomerase-congenital disorder of glycosylation (MPI-CDG) and provide a review of the relevant literature. The young girl presented with recurrent unexplained diarrhea, vomiting, hypoproteinemia, and elevated liver transaminases. Whole-exome sequencing revealed that the patient had compound heterozygous mutations in the MPI gene (NM_0024). An exon 4 (c.455G>T, p.R152L) mutation was inherited from the mother and an exon 7 (c.884G>A, p.R295H) mutation from the father. One week after the start of mannose treatment, the vomiting and diarrhea symptoms disappeared completely and did not show any side effects. We also provide a brief review of the relevant literature. Including the present case, a total of 52 patients from hospitals across 17 countries were diagnosed with MPI-CDG. Age at disease onset ranged from birth to 15 years, with an onset under two years in most patients (43/50). Overall, patients presented with at least one or more of the following symptoms: chronic diarrhea (41/46), vomiting (23/27), hepatomegaly (39/44), hepatic fibrosis (20/37), protein-losing enteropathy (30/36), elevated serum transaminases (24/34), hyperinsulinemic-hypoglycemia (24/34), hypoalbuminemia (33/38), prolonged coagulation (26/30), splenomegaly (13/21), non-pitting edema (14/20), failure to thrive (13/36), portal hypertension (4/9), epilepsy (2/17), thrombosis (12/14), and abnormally elevated leukocytes (5). None of the patients was reported to have an intellectual disability (0/28). The majority of patients (26/30) showed clinical symptoms, and laboratory results improved after oral mannose administration. Our findings suggest that MPI-CDG should be considered in children with unexplained recurrent digestive and endocrine systems involvement, and gene examination should be performed immediately to obtain a definite diagnosis in order to begin treatment in a timely manner.